1996
DOI: 10.1046/j.1423-0410.1996.7130176.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Rh D Antigen Sites on Weak D and D Variant Red Cells by Flow Cytometry

Abstract: Information on the number of D sites on weak D (Du) and D variant cells is limited and incomplete. The aim of this study was to use a simple non-isotopic technique utilising a combination of flow cytometry and ELISA to quantitate the number of D sites on an extensive range of these cells. Five human monoclonal IgG anti-D (BRAD-7 (JAC10), BRAD-5, 2B6, BRAD-3, H27) and one affinity-purified polyclonal IgG anti-D were each used at a saturating concentration of 20 micrograms/ml. In general, BRAD-3, BRAD-5 and 2B6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 39 publications
5
38
3
Order By: Relevance
“…Its epitope distribution lacking epitopes 4, 11, and 31 did not resemble D HR, which lacks epitopes 1, 2, 12, and 20. The low antigen density of both D HO (1300 D antigens/cell) and D HR (3800 D antigens/cell 12 ) might have confounded epitope determination. However, it should be noted that the nonconservative amino acid substitution in D HO (lysine eliminated) differs from the conservative one in D HR.…”
Section: Discussionmentioning
confidence: 99%
“…Its epitope distribution lacking epitopes 4, 11, and 31 did not resemble D HR, which lacks epitopes 1, 2, 12, and 20. The low antigen density of both D HO (1300 D antigens/cell) and D HR (3800 D antigens/cell 12 ) might have confounded epitope determination. However, it should be noted that the nonconservative amino acid substitution in D HO (lysine eliminated) differs from the conservative one in D HR.…”
Section: Discussionmentioning
confidence: 99%
“…45), and therefore it is important to distinguish weak D from partial D. The working definition of a weak D versus a partial D phenotype is that individuals with the former do not produce antibodies when exposed to D-positive erythrocytes by either transfusion or pregnancy, unlike partial D individuals. 45), and therefore it is important to distinguish weak D from partial D. The working definition of a weak D versus a partial D phenotype is that individuals with the former do not produce antibodies when exposed to D-positive erythrocytes by either transfusion or pregnancy, unlike partial D individuals.…”
Section: Weakened D Antigen Expressionmentioning
confidence: 99%
“…(1999) suggested that the routine administration in the UK of a 500 IU dose of prophylactic anti‐D postpartum was probably sufficient to prevent anti‐D immunization when the FMH is much greater than 4 ml of weak D fetal red cells. As there are at least nine times more RhD sites on RhD‐positive red cells compared with weak D red cells (Jones et al. , 1996; Wagner et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 1995). With the introduction of high avidity monoclonal anti‐D reagents, such as RUM‐1, many individuals given D u status may now simply be regarded as RhD positive because of complete reactivity (Jones et al. , 1996).…”
Section: Introductionmentioning
confidence: 99%